The Role of Effective Inventory Management System on Customers’ Satisfaction; The Case Study of Ethiopia Electric Utility, Northeast Region Store Dessie - Gupta S.K.; Gupta S.K.; Rana R.; Kumar V.; Ayalew Y.; Mekonen T.N. (My University, 2025)
Various continuous utility management activities have been pursued by the Ethiopian Electric Power Company (EEPCo), the state-owned monopoly that produces, transmits, distributes and sells electric power nationally. However, based on an organizational review of the vertically integrated state-owned Ethiopian electricity company undertaken by IPA Energy and Water Economics, a major organizational reform could bring acceleration in business operations and achievement of corporate goals. In general, the main outcome of this research will be examining the role of an effective inventory management system on customers’ satisfaction. Inventory management is an important factor in successful customers’ satisfaction. The researcher uses a case-study style with some practical modifications to match the contextual requirements. In this research, data mining, machine learning and data science methods were applied to the data detected on Twitter. Also in this study, text mining methods were applied to the data collected on Twitter. In total, 142,000 tweets were collected. It was observed that the homogeneity of the data set increased the success rate. Besides, different machine learning algorithms were tried within the scope of the study and results with high success rates were tried to be obtained. The highest success rate was obtained with the naive Bayes (kernel) algorithm with 52.09%. As a result of applied machine learning algorithms, it has been observed that the effective stock management system is associated with customer satisfaction from sentence structures and words used, concerning the thesis in question. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.